The effects of toe direction on three-dimensional knee kinematics during closed kinetic chain exercise in patients with anterior cruciate ligament deficient knee - Aiko Sakurai; Kengo Harato; Yutaro Morishige; Shu Kobayashi; Yasuo Niki; Takeo Nagura (Elsevier, 2019)
Background/Objective: Closed Kinetic Chain Exercise (CKC Ex) is a safe rehabilitation method for anterior cruciate ligament deficient (ACLD) and reconstructed knees. However, CKC Ex can be risky based on abnormal toe directions. The purpose was to investigate knee kinematics during CKC Ex under three toe directions in ACLD. Methods: Twenty patients with unilateral ACL injury participated. The subjects performed five weight-bearing-static lunge tests on each limb under three toe directions, including 0 degrees (TN), 20 degrees (TI), and -20 degrees (TO). Three-dimensional knee kinematics were calculated using three-dimensional motion analysis system and were compared among three different toe directions. Results: Among three different toe directions, peak values of knee valgus and external rotation on ACLD side were significantly larger in TO than in TN and TI. In addition, the total excursion in the coronal plane on ACLD side was significantly larger in TO than in TN and TI. Regarding the differences between ACLD and ACLI, peak values of internal rotation angle was significantly smaller in ACLD than in ACLI. Conclusion: From the present results, tibial rotation and knee abduction were strongly affected by toe direction. When considering a safe rehabilitation, it would be better to avoid TI and TO in CKC Ex in patients with unilateral ACL injury. Keywords: Closed kinetic chain exercise, Static lunge, Anterior cruciate ligament, Motion analysis, Compensatory mechanics